PENGARUH KEBIJAKAN DIVERSIFIKASI TERHADAP KINERJA PERUSAHAAN DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Manufaktur Multinasional yang terdaftar di Bursa Efek Indonesia Tahun 2014 – 2017) - Firza Arieska; Puji Harto (Diponegoro Journal of Accounting, 2019)
This study aims for analyzing the effect of diversification to firm performance with investment opportunity set as moderation variable and without moderation variable. The diversification itself includes geographic diversification and segment diversification. Firm performance has financial performance and market performance.This research uses secondary data and its sample from manufacturing company that listed at Indonesia Stock Exchange (IDX) in the period 2014-2017. With using purposive sampling, researcher has found 132 financial statements from company which has been analyzed. The analysis method of this study using multiple regression analysis.The result findings in this study indicate without moderation of investment opportunity set, geographic diversification has no significant effect with financial performance and has significant positive effect with market performance. Segment diversification has significant negative effect with financial performance and has significant positive effect with market performance. If there is a moderation effect of investment opportunity set, the moderation effect of investment opportunity set has no significant effect for the effect of diversification for firm performance.